Assessment of Lipase Enzyme Production Potential of Bacteria Isolated from Oryza Sativa (Rice) Rhizosphere in Sokoto, Nigeria - Miya, Yusuf Yahaya; Gatawa, Sakina Abubakar; Yusuf, Anas (Darul Yasin Al Sys, 2024)
The work analyzed a total five (5) different soil samples in the rhizosphere of rice from Sokoto metropolis. Therewith, the potentially of bacterial isolate was screened for the lipase production using standard methods and procedures, and chemicals of analytical grade. Bacillus spp had the highest percentage of occurrence 40%. The next was E. coli with percentage of 30%. Followed by, Flavobacterium with percentage of 20% which also show that flavobacterium appears in two locations. S.aureus had a percentage occurrence of 10% respectively. The results of this study outlined the potential of synthesizing lipase enzyme from bacteria (especially the Bacillus spp which had a highest lipase activity). In turn, microbes examined could be utilized as for industrial production and other benefits.